2017
DOI: 10.1177/2374373517715010
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Patients During the Clinical Management Pathway of Abdominal Aortic Aneurysms at a NHS Trust

Abstract: BackgroundThe epidemiology of abdominal aortic aneurysm (AAA) is changing. Outcomes for aortic surgery have improved. However, the accepted guideline for the management of AAAs has remained unchanged over the last 2 decades. We aimed to gain insight into the patients’ experience while they are managed under the traditional clinical pathway.MethodWith the help of a patient focus group, we designed a survey to assess the patients’ perception of the disease and their experience during different stages of the AAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This review shows that only three studies specifically address the impact of follow up and potential re-interventions on a patient's perspective of QoL. 53,58,59 One emerging conclusion is that, in contrast, to general assumptions, patients experience follow up as reassuring. In fact, patients report that dissatisfaction with follow up was due to a lack of follow up after OR rather than to excessive follow up after EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review shows that only three studies specifically address the impact of follow up and potential re-interventions on a patient's perspective of QoL. 53,58,59 One emerging conclusion is that, in contrast, to general assumptions, patients experience follow up as reassuring. In fact, patients report that dissatisfaction with follow up was due to a lack of follow up after OR rather than to excessive follow up after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Two qualitative studies addressed the patients' attitudes towards the possibility of a reintervention in elective repair. 58,59 It was concluded that the possibility of a re-intervention influenced the choice of repair (i.e., patients preferred to not have a re-inter vention). No qualitative study specifically addressed the impact on QoL of an actual re-intervention.…”
Section: The Impact Of Follow Up On Quality Of Lifementioning
confidence: 99%
“…This may be due to a better understanding of the importance of surveillance. Patients who had AAA repair may feel that they are disease free 31 and therefore do not need more treatment. As a result, patients may fail to appreciate the importance of surveillance and become non-compliant.…”
Section: Discussionmentioning
confidence: 99%
“…This was further underpinned by the fact that 52% of the respondents felt highly preoccupied by the size of their AAAs. 13 …”
Section: Discussionmentioning
confidence: 99%